Regional action program on 'water resources management': an overview of actions towards better water use in Mediterranean agriculture - Lacirignola C.; Hamdy A.; Todorovic M. (Regional Action Programme (RAP): Water resources management and water saving in irrigated agriculture (WASIA PROJECT), 2003)
Regional action program on 'water resources management': an overview of actions towards better water use in Mediterranean agriculture